Pricing strategy for the New York expansion of Pestana CR7 brand - Tavares, Miguel Lousa (2021)
The objective of the underlying project was to achieve a pricing strategy to be applied to the 2020´s expansion of the Pestana CR7 Hotel brand to New York. Therefore, it is necessary to analyze the CR7 brand and its competitive advantages as well as the proposed hotel neighborhood and potential competitors before actually entering the market. Finally, by using a short-list of competitors as benchmark, a reference table was built for the monthly prices during the hotel´s first year of activity and some recommendations provided regarding future revenue management and the pricing strategy.